TRADISI PEMBACAAN LIMA SURAH PILIHAN DALAM RITUAL KASAMBU PADA MASYARAKAT MUNA (Studi Living Qur’an di Kel. Waimhorock Kec. Abepura Kota Jayapura) - Putra, Ranowan; Lubis, Zakaria Husin; Nurbaiti, Nurbaiti (Lembaga Penelitian dan Studi kebijakan MADANI Instutute, 2024)
This Study aims to discuss the tradition of reading five selected surahs in the Kasambu ritual in the Muna community (study living Qur’an in Waimhorock District, Abepura District, Jayapura City). This study uses a qualitative method with a sociological phenomenological approach. Primary data sources come from important documents owned by community institutions, as well as answer from related parties interviewed. While secondary sources come from various scientific references related to the discussion. There is a debate among Muslim scholars about the study of the living Qur’an, namely groups that support and groups that criticize the study of the living Qur’an. The groups that support the living Qur’an are Jalaluddin as-Suyuthi and Badruddin az-Zarkasyi. Meanwhile, groups that criticize the living Qur’an are Fazlur Rahman, Nasr Hamid Abu Zaid, and Farid Esack. In addition, one of the Indonesian figures who also criticized the Qur’an was Mun’im Sirry. The findings of this study indicate that the social and Qur'anic meaning of the tradition of reading the five selected surahs in the Kasambu ritual in the Muna community is a form of community effort or endeavor to gain the pleasure of Allah. Kasambu ritual in the Muna community is a form of community effort or effort to get the pleasure of Allah SWT. This is evidenced by the reading of selected surahs in the Qur'an such as surah al-Fâtiḫah, surah al-Qadr, surah al-Ikḫlâsh, surah al-Falaq and surah an-Nâs. Where from the reading of these suras, people believe and believe that Allah SWT will be pleased with everything they do and Allah SWT will always pour out His mercy and protect and protect them from interference from supernatural beings (syaithan) both from among others. jinn and from among humans, especially to mothers and prospective babies who are in the womb